Effect of alumina/graphene hybrid nano reinforcement to the adhesion and mechanical properties of adhesively bonded aluminum alloy with epoxy - Mohamad Syaiful Izwan, Alies; Nur Zalikha, Khalil (Elsevier Ltd, 2021)
In present work, an attempt has been made to investigate the effect of alumina and graphene nanoplatelets (GNP) hybrid nano reinforcement to the wetting behavior and mechanical property of adhesively joint aluminum alloy with epoxy adhesive. Alumina-GNP hybrid nano adhesive at 1.0 wt% concentration with various weight ratio combination (i.e.: 10:0, 7:3, 5:5, 3:7, 0:10) was adopted into two components structural epoxy adhesive to bond 7075-T6 aluminum alloy. When compared to pristine adhesive, hybrid nano adhesive has shown two distinct trends with regard to the spread area behavior: (i) hybrid nano adhesive at 7:3 and 5:5 wt ratio combination exhibits a reduction of spread area up to 71.59 % and 48.07% respectively while (ii) hybrid nano adhesive at 3:7 wt ratio combination has shown an increase of spread up to 31.58%. It is also observed that the incorporation of hybrid nano reinforcement at 7:3 wt ratio combination has demonstrated highest shear strength up to 42.29% as compared to the pristine adhesive counterpart. Moreover, as compared to specimens with single alumina and GNP nano adhesives (i.e.: 10:0 and 0:10 wt ratio), specimens with hybrid nano adhesive at 7:3 wt ratio demonstrates an improved shear strength up to 61.48% and 101.2%, respectively. In current work, it has been observed that regardless of alumina-GNP weight ratio combination, all fractured specimens demonstrated the combination of adhesive and cohesive fractures behavior